1999
DOI: 10.1046/j.1432-1327.1999.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrins, the mechanism of iron release by ovotransferrin

Abstract: Iron release from ovotransferrin in acidic media (3 , pH , 6) occurs in at least six kinetic steps. The first is a very fast (# 5 ms) decarbonation of the iron-loaded protein. Iron release from both sites of the protein is controlled by what appear to be slow proton transfers. The N-site loses its iron first in two steps, the first occurring in the tenth of a second range with second order rate constant k 1 = (2.30^0.10) Â 10 4 m 21´s21 , first order rate constant k 21 = (1.40^0.10) s 21 and equilibrium consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Interactions between Lobes-A cooperative effect of one lobe on the other lobe has been convincingly documented in a number of studies using a variety of techniques, which include NMR of hTF (58), absorption spectra of oTF (59), pH-dependent iron release of LTF (60), calorimetric studies of both hTF and oTF (61-63), electrospray ionization mass spectrometry studies of hTF (43), iron release from monoferric LTF (64), analysis by urea gels (22), and chemical relaxation studies (65)(66)(67). Significantly, a number of these studies specifically attribute cooperative effects between the two lobes of hTF to participation of helix 12 from the C-lobe (2,68).…”
Section: Triad-lysmentioning
confidence: 97%
“…Interactions between Lobes-A cooperative effect of one lobe on the other lobe has been convincingly documented in a number of studies using a variety of techniques, which include NMR of hTF (58), absorption spectra of oTF (59), pH-dependent iron release of LTF (60), calorimetric studies of both hTF and oTF (61-63), electrospray ionization mass spectrometry studies of hTF (43), iron release from monoferric LTF (64), analysis by urea gels (22), and chemical relaxation studies (65)(66)(67). Significantly, a number of these studies specifically attribute cooperative effects between the two lobes of hTF to participation of helix 12 from the C-lobe (2,68).…”
Section: Triad-lysmentioning
confidence: 97%
“…The rate-limiting step is the conformational change induced by the rapid removal of bound iron. It was recently reported that the protonation of iron-binding residues of ovotransferrin at acidic pH in the absence of anionic chelators is slow (Abdallah & Chahine, 1999). Studies suggested the release of iron ion from ferric transferrin requires the presence of a simple anion such as pyrophosphate, sulfate, or chloride; however, the rate of anion-mediated iron release is much slower for the C-lobe than for the N-lobe (Mizutani, Muralidhara, et al, 2001;Muralidhara & Hirose, 2000), as there are two anion binding sites in the N-lobe but only one anion-binding site in the C-lobe.…”
Section: Structure Of Ovotransferrinmentioning
confidence: 99%
“…The iron binding ability confers antimicrobial activity by rendering iron unavailable for microbial growth (Abdallah & Chahine, 1999;Mason & Macgillivray, 2002). Transferrins can be divided into four types according to their occurrence in nature as shown in Table 1 (Mason & Macgillivray, 2002): (1) serum transferring (pI 7.4) is found in blood plasma where its main function is iron transfer; (2) lactoferrin (pI 8.8) is found in milk and other mammalian secretions; it binds iron more tightly over a larger pH range than other transferrin proteins and has a diverse range of biological activities including innate defense;…”
Section: Introductionmentioning
confidence: 99%
“…The changes of the fluorescence spectra of apotransferrins have been analyzed by addition of transition metal, lanthanide ions or aluminum(III). [8][9][10][11][12] There is a significant difference in either metal ion binding 12,13 or removal of metal ions 14,15 for N-and Cterminal binding sites of apoovotransferrin. Whether it relates the tyrosine hydrogen bonds in solution structure of two binding sites is far from clear.…”
Section: Introductionmentioning
confidence: 99%